Comparison of Preop High Resolution CT Temporal Bone Findings with Intraoperative Findings in Cholesteatoma - Waqas Javaid, M. Naeem, S. Tauseef Bukhari, R. Ali, S. Muhammad Azeem, ,Bilal Zahid,, M. Fatima, Pratishta Joshi, Mirza M. Sarwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Since many years, CT-scan of the temporal bone is a widely accepted investigation in preoperative evaluation of patients with cholesteatoma in the middle ear. Aim: To compare the preoperative HRCT findings with intraoperative findings in the patients with atticoantral CSOM Study design: Comparative cross-sectional study Setting: Department of ENT Sir Ganga Ram Hospital Lahore Duration: February 1st 2022 to January 31st 2023 Methods: After taking approval from board of studies, IRB & ASRB of FJMU, 50 patients fulfilling inclusion criteria were admitted in Department of ENT, Sir Ganga Ram Hospital Lahore. Firstly patients were seen in outdoor, history and otoscopy followed by examination under microscope was done, then the diagnosis of atticoantral CSOM was established. HRCT temporal bone of the cases diagnosed as atticoantral type CSOM was done. The patients were then admitted for mastoid exploration. Informed consent was obtained. Demographic information was recorded. HRCT temporal bone was reported by consultant radiologist from Department of Radiology, Sir Ganga Ram Hospital in all cases. Intraoperative findings like soft tissue mass, dural& sinus plate, ossicular status, status of semicircular canal, facial canal and scutum was noted and compared with the preoperative HRCT findings. Then the data was collected in accordance to patients Proforma. Results: The mean age of patients was 22.32±10.42 years. Among patients 56% were male and 44% were female. HRCT was closely in agreement with intraoperative findings for detection of soft tissues mass in middle ear [HRCT:92% & IOF: 100%], dural plates [HRCT:98% & IOF: 98%], Sigmoid sinus plates [HRCT:92% & IOF: 92%], erosion of malleus [HRCT:56% & IOF: 62%], Incus [HRCT:56% & IOF: 26%], stapes [HRCT:60% & IOF: 66%], ;lateral semicircular canal [HRCT:96% & IOF:96%], facial canal nerve [HRCT:96% & IOF: 94%] and scutum [HRCT:70% & IOF: 74%] respectively. This would be of great help to the otologists in anticipating the possible complications, developing treatment strategy, counseling the patient regarding the procedure and in taking consent about expected complications. Conclusion: In patients of atticoantral CSOM HRCT effectively helps in preoperative assessment of the site & extent of the disease process, Ossicular erosion and status of various important anatomical structure. Keywords: Preoperative, HRCT, Intraoperative, Atticoantral, CSOM, Mastoidectomy, Ossicular necrosis.